Analysis of fiscal efficiency of taxation in the system of filling budget funds in Ukraine - Stashchuk, Olena; Boiar, Andrii; Shmatkovska, Tetiana; Dziamulych, Mykola; Skoruk, Olena; Tesliuk, Sofiia; Zintso, Yuliya (My University, 2021)
The article aims to identify the analysis of the fiscal efficiency of income tax. The growth of public expenditures and the need to fill the budget leads to the need to ensure effective management of tax revenues. At the same time, the overall efficiency of the operation of the tax mechanism for corporate income tax involves the formation of an effective fiscal system. Since the management of tax revenues should provide a balance between the needs of the state in taxes and the need of enterprises to increase profits, it is necessary to develop effective approaches to the fiscal efficiency of income tax. It is determined that the peculiarities of the analysis of fiscal efficiency of this tax are specific efficiency criteria, which reflect different approaches to the principles of formation of public funds.
Keywords: Budget; Finance; Financial resources; Financial security; Fiscal efficiency; Taxation; Tax burden ratio; Tax policy